2022
DOI: 10.1002/slct.202201514
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐blue Fluorophores Based on Phenanthroimidazole Integrated with Benzo[d]thiazole: Experimental and Theoretical Investigation

Abstract: Three deep-blue emissive donor-acceptor (DÀ A) fluorophores, 2-(4'-(1-(4-(tert-butyl)phenyl)-1H-phenanthro [9,10-d] 10d]imidazol-1-yl)benzonitrile (m-CNPISN) based on benzothiazole with varying substituents at N1-position to tune the properties of the materials were designed and synthesized. The synthesized fluorophores were structurally confirmed by spectroscopic techniques. All the fluorophores exhibited good thermal properties with high thermal degradation temperatures. An optical study reveals that the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Our group identified some thiadiazole derivatives with inhibitory activities and fluorescence properties [32–34] . In recent years, it has been found that benzothiazole π‐conjugated moiety exhibits good photophysical properties and has attracted wide interest of researchers [35–36] . The novel pyrido[2,1‐ b ] benzothiazole derivatives 15 a – 15 d (shown in Figure 1) exhibited remarkable fluorescence intensity with considerably high quantum yields with anti‐bacterial and anti‐fungal activities [37] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group identified some thiadiazole derivatives with inhibitory activities and fluorescence properties [32–34] . In recent years, it has been found that benzothiazole π‐conjugated moiety exhibits good photophysical properties and has attracted wide interest of researchers [35–36] . The novel pyrido[2,1‐ b ] benzothiazole derivatives 15 a – 15 d (shown in Figure 1) exhibited remarkable fluorescence intensity with considerably high quantum yields with anti‐bacterial and anti‐fungal activities [37] .…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] In recent years, it has been found that benzothiazole πconjugated moiety exhibits good photophysical properties and has attracted wide interest of researchers. [35][36] The novel pyrido[2,1-b] benzothiazole derivatives 15 a-15 d (shown in Figure 1) exhibited remarkable fluorescence intensity with considerably high quantum yields with anti-bacterial and antifungal activities. [37] In 2020, a new fluorescent probe 2 based on conjugated benzothiazole (shown in Figure 1)showed high selectivity toward SO 3 2À /HSO 3 À in aqueous solution and achieved cells imaging.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the introduction of materials with excellent electron transfer properties, such as triazole, 6,7 oxazole 8,9 etc ., is an effective way to improve the electron transfer ability. On the other hand, constructing blue emitters with a donor–acceptor (D–A) structure can provide molecular bipolarity to balance carrier transport, 10–12 and matching the energy levels of the luminescent layer with those of adjacent functional layers is also a key step to achieve balanced charge transmission. Additionally, effective π-stacking in molecules is of great importance to increase intermolecular interactions and accelerate charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many deep-blue fluorescent emitters based on hot-excitons have been reported. In order to regulate the balance between the LE state and charge transfer (CT) excited state to improve Φ PL and η r , while ensuring short wavelength emission, mild chromophore units such as phenanthroimidazoles, 12–15 carbazoles, 16–20 and triphenylamines 21–25 are usually chosen to construct hot-exciton deep-blue materials. Anthracene has a subtle energy level arrangement with a large T 1 –T 2 energy gap, which is very favorable for the hRISC process.…”
Section: Introductionmentioning
confidence: 99%